2023
DOI: 10.1149/2754-2734/acb562
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermally Synthesized ZnSnO3 Nanoflakes Based Low-Cost Sensing Device for High Performance CO2 Monitoring

Abstract: We report a room-temperature operative ZnSnO3 nanoflakes-based CO2 gas sensor. The perovskite ZnSnO3 nanoflakes are synthesized by one-pot hydrothermal technique. The prepared material characterized via X-ray diffraction (XRD), scanning electron microscopy, UV-visible spectroscopy, and dynamic light scattering measurement to confirm the crystal structure, surface morphology, and optical properties. The XRD pattern revealed that ZnSnO3 was in orthorhombic phase and average crystallite size examined by Scherrer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 57 publications
0
9
0
Order By: Relevance
“…Both response and recovery time for the YCeO-based sensors are protracted with the increase in H 2 concentration. The recovery time is the amount of time needed to lessen the gap between the maximum and lowest current, and the response time (tres) is the amount of time required for the relative current change to reach 90% of the steady state value following H 2 injection [13][14][15][16]. As shown in Figure 2c,d, the YCeO sensor demonstrated a decent response at 28…”
Section: H 2 Gas Sensingmentioning
confidence: 97%
“…Both response and recovery time for the YCeO-based sensors are protracted with the increase in H 2 concentration. The recovery time is the amount of time needed to lessen the gap between the maximum and lowest current, and the response time (tres) is the amount of time required for the relative current change to reach 90% of the steady state value following H 2 injection [13][14][15][16]. As shown in Figure 2c,d, the YCeO sensor demonstrated a decent response at 28…”
Section: H 2 Gas Sensingmentioning
confidence: 97%
“…For performing these computational calculations, we utilized the LanL2DZ basis set and the B3LYP functional. 66 Here, we focused on the HOMO and LUMO energy levels from the DFT study so that we could analyze additional electronic features of these species.…”
Section: Density Functional Theory (Dft)-based Studymentioning
confidence: 99%
“…The optimization was performed with the Gaussian 09 program, and the molecular structures were designed with the Gauss View 05 program. For performing these computational calculations, we utilized the LanL2DZ basis set and the B3LYP functional . Here, we focused on the HOMO and LUMO energy levels from the DFT study so that we could analyze additional electronic features of these species.…”
Section: Acetone and Sanitizer Sensing Mechanism With Performance Of ...mentioning
confidence: 99%
“…2 Similarly, it has been reported that 1000 ppm is the threshold limit for the level of CO 2 in occupied buildings. 3 Concentrations above this limit could lead to adverse effects on residents such as fatigue, respiratory inflammation, and headache. 4 CO 2 gas is also relevant in other real-world applications ranging from food packaging to improve perishable food product shelf life (modified atmosphere packaging) to environmental monitoring of greenhouse gases, fire detection, medical diagnostics, and photosynthesis.…”
mentioning
confidence: 99%
“…The increase in this atmospheric CO 2 gas level above 400 ppm may have a negative impact on the environment . Similarly, it has been reported that 1000 ppm is the threshold limit for the level of CO 2 in occupied buildings . Concentrations above this limit could lead to adverse effects on residents such as fatigue, respiratory inflammation, and headache .…”
mentioning
confidence: 99%